A cross sectional study to assess knowledge and practice regarding antibiotic used among parents of children attending paediatric clinic - Darussalam, Siti Eliza; Tompell, Afryan; Juni, Muhamad Hanafiah; Zainal Abidin, Mohd Azri (Community Health Society Malaysia (CHSM), 2017)
Introduction: Antibiotic is an antibacterial drug that is used widely to treat bacterial infection since it was discovered by Professor Alexander Fleming. However, inappropriate use of antibiotic will result in various hazards; the most important one is antibiotic resistance. The aim of this study is to assess the knowledge and practices on antibiotic used among parents of children attending paediatric clinic in a hospital in Malaysia. Methodology: A cross-sectional study was conducted among parents accompanying child attending paediatric clinic. A total of 247 respondents was selected using random sampling technique. Self-administered questionnaire was used to collect data. The questionnaire consists of sections on; socio-demographic characteristics, knowledge on antibiotic used and practices on antibiotic used. The data was entered and analysed using SPSS. Results: A total of 229 (92.8%) parents completed the questionnaire. The study revealed that the knowledge score of parents studied ranging from the lowest 14.8% to the highest score of 97.8%. Findings also showed that 95.6% parents had experienced giving their child antibiotic before, and 96.5% get antibiotic by doctor prescription and 97.8% follows doctor instruction when giving antibiotic. About 41.0% of parents experienced buying antibiotic from pharmacy without doctor prescription and only 9.6% giving antibiotic when their child having flu. Conclusion:Majority of parents having good knowledge score on antibiotic used, and majority of them parents getting prescription before using antibiotic.